2006
DOI: 10.1080/08916930600907954
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in PKC theta demonstrate impairedin vivoT cell activation and protection from T cell-mediated inflammatory diseases

Abstract: In the present study we have characterized T cell-driven immune function in mice that are genetically deficient in PKC theta. In response to simple immunologic stimulation invoked by in vivo T cell receptor (TCR) cross-linking, these mice showed significantly depressed plasma cytokine levels for IL-2, IL-4, IFNgamma, and TNFalpha compared to wild-type (WT) mice. In parallel, spleen mRNA levels for these cytokines were reduced, and NF-kappaB activation was also reduced in PKC theta knockouts (KO). Injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…44,45 Mechanistically, the role of PKC-in immune responses is clearly established in mouse models of autoimmunity, asthma, and arthritis [46][47][48][49][50] ; nevertheless, the exact biochemical mechanisms of PKC-function(s) are enigmatic. Although several transcription factors essential for interleukin-2 (IL-2) induction (ie, nuclear factor B [NF-B], activator protein 1 [AP-1], and nuclear factor of activated T cells [NF-AT]) are regulated in part by PKC-, 44 additional physiologic and nonredundant functions of PKC-in T cells must be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44,45 Mechanistically, the role of PKC-in immune responses is clearly established in mouse models of autoimmunity, asthma, and arthritis [46][47][48][49][50] ; nevertheless, the exact biochemical mechanisms of PKC-function(s) are enigmatic. Although several transcription factors essential for interleukin-2 (IL-2) induction (ie, nuclear factor B [NF-B], activator protein 1 [AP-1], and nuclear factor of activated T cells [NF-AT]) are regulated in part by PKC-, 44 additional physiologic and nonredundant functions of PKC-in T cells must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, T lymphocytes express multiple isotypes of PKC, 29,44,[47][48][49][50] which are thought to exert substrate preferences through distinct subcellular localizations established via selective kinase/lipid and kinase/protein interactions. Recent studies have shown that at least 4 PKC isotypes are critical for T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of LM-and LCMV-specific CD4 and CD8 T cells was determined by an IFN-␥ specific ELISPOT as described previously (23 [33][34][35][36][37][38][39][40][41] (10 Ϫ8 M) peptide, respectively. Isolated splenic and hepatic leukocytes from infected BALB/c were coincubated with spleen cells from noninfected BALB/c WT mice (2 ϫ 10 5 /well), which were loaded with LLO 189 -200 (10 Ϫ6 M) or LLO 91-99 (10 Ϫ8 M) peptide.…”
Section: Elispotmentioning
confidence: 99%
“…Functionally, PKC-is required for T-cell activation, proliferation, and survival (25,34,44). Experimental studies with mice have unequivocally demonstrated that PKC-is crucial for the activation of autoreactive T cells and induction of T-cell-mediated autoimmune diseases (2,16,36,48).…”
mentioning
confidence: 99%